一种芳香族聚酯的解聚成环方法 (2023)
本发明公开了一种芳香族聚酯的解聚成环方法，包括以下步骤：将芳香族聚酯与高沸点绿色溶剂、催化剂混合，加热溶解使芳香族聚酯发生解聚成环反应得相应环状低聚酯；其中，所述高沸点溶剂为1,3-二甲基-2-咪唑啉酮等不含卤素和芳香基团的绿色溶剂，所述加热温度为180~250℃，所述催化剂为有机碱催化剂，分离提纯后环状低聚酯产率可达91%。本发明的芳香族聚酯的解聚成环方法可用于聚酯的化学回收，使用绿色环保的溶剂作为反应溶剂，在有机碱催化剂的催化下将回收的芳香族聚酯解聚得到芳香族环状低聚酯，从而实现对芳香族聚酯的绿色化学回收，为芳香族聚酯的回收和高值化利用打下基础。 A depolymerization cyclization method for an aromatic polyester. The depolymerization cyclization method comprises the following steps: mixing an aromatic polyester with a high-boiling-point environmentally friendly solvent and a catalyst, heating and dissolving the mixture to subject the aromatic polyester to a depolymerization cyclization reaction so as to obtain the corresponding cyclic oligoester, wherein the high-boiling-point solvent is an environmentally friendly solvent that does not contain a halogen or an aromatic group, such as 1,3-dimethyl-2-imidazolinone, the heating temperature is 180-250ºC, the catalyst is an organic base catalyst, and the yield of the separated and purified cyclic oligoester can reach 91%. The depolymer